Ondansetron Pharmacokinetics in Pregnant Women and Neonates: Towards a New Treatment for Neonatal Abstinence Syndrome. Issue 2 (4th December 2014) - Elkomy, MH; Sultan, P; Carvalho, B; Peltz, G; Wu, M; Clavijo, C; Galinkin, JL; Drover, DR
<x xml:space="preserve">Abstract</x> Ondansetron is the drug of choice to prevent nausea in women undergoing cesarean surgery and can be used to prevent neonatal abstinence syndrome (NAS). The pharmacokinetics of ondansetron have not been characterized in pregnant women or in newborns. A nonlinear mixed‐effects modeling approach was used to analyze plasma samples obtained from 20 nonpregnant and 40 pregnant women following a single administration of 4 or 8 mg ondansetron, from umbilical cord blood at delivery, and from neonates after birth. The analysis indicates that: ondansetron disposition is not affected by pregnancy (P > 0.05), but influenced by dose (P < 0.05), and is characterized by rapid transplacental transfer and longer elimination half‐life in neonates compared to their mother. A dosing regimen for prevention of NAS was designed based on the model. The regimen involves IV administration of 4 mg to the mothers shortly before cord clamping, or oral administration of 0.07 mg/kg (or equivalently 0.04 mg/kg IV) to neonates.